Stressful Life Events In Relation to Dental Caries and Selected Salivary Constituents Among Secondary School Students in Baghdad City - Ahmed K. Abdul-Ameer; Nada J. Radhi; Huda J. Abdul-Ghani (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: stress is the reactions of the body to forces of a deleterious nature, infections and various abnormal states that tend to disturb its normal physiological equilibrium; It is described as adverse emotions or reactions to unpleasant experiences; Thus, any real or perceived physical, social, or psychological event or stimulus that causes bodies to react or respond have deleterious effects on the general and oral health. The aims of this study were to assess the severity of dental caries among the students with different categories of stressful life events in relation to physicochemical characteristics of whole stimulated saliva. Materials and Methods: the total sample is composed of 300 students (males only) aged 17-18 years old, who are randomly selected from 10 school in the First Al-Karkh/Baghdad. The total sample classified into three categories (less stress, more stress, accumulative stress) according to stressful life events scale (SLE); the sub sample consist of 60 students who are randomly selected from the total sample each category composed of 20 students. Diagnosis and recording of dental caries was assessed according to Decay, Missed, Filled surface index (D1-4MFS) of Muhlemann (1976). Stimulated salivary samples were collected from the 60 students then measuring salivary flow rate; and chemically analyzed to determine salivary interlukin-6 (IL-6), cortisol, and total protein. All data were analyzed using SPSS version 21. Results: Results recorded the highest mean rank value of (DMFS) was among the accumulative stress category of stressful life events scale followed by more stress category, the lowest mean rank value was among less stress category with statistically high significant difference (P< 0.001). For the severity of dental caries (DS) Fraction was higher among the accumulative stress category than more stress and less stress categories respectively (P< 0.001). According to the grades of lesion severity, for all fractions the higher mean rank values was among accumulative stress category with no statically differences except for (D2) was significant (P< 0.05). The data from salivary analysis showed that, the highest values of salivary total protein and (IL-6) were among the accumulative stress category, followed by more stress then the lowest value among less stress category, while the cortisol showed the opposite picture, however all these differences were not significant. DMFS correlated positively with flow rate among less stress and accumulative stress categories and negatively with more stress category, while for (DS) correlated negatively with flow rate with highly significant for more stress category and accumulative category and positively related with significant for low stress category. The salivary constituents showed negative correlation with (DMFS) for all categories of stressful life events scale except for IL-6 and cortisol were positively correlated for accumulative category with non-significant difference. Conclusion: The study revealed that, stressful life events have a significant deleterious impact on the oral and dental health including caries experience as well as the effect on the normal levels of salivary constituents.